Fauna flebotomínea na bacia do Rio Araguari, antes, durante e após a construção da barragem da Usina Hidrelétrica Capim Branco I, Uberlândia, Minas Gerais, Brasil - Lemos, Jureth Couto (2007)
American Cutaneous Leishmaniosis ACL and American Visceral - AVL are non-contagious infect-parasitic diseases of zootic character, caused by protozoa of several species of the gender Leishmania that attack man, several species of domestic and wild animals. These diseases are considered re-emerging infections that reappear or are spread out in a way they can reach other areas in which its presence had not been noticed before. The World Health Organization considers ACL as being the second most important disease caused by protozoa when it concerns public health. The vectors of ACL and of AVL are phlebotomine of the Lutzomyia genus. Worldwide about 800 species are known of which 229 are found in Brazil. Of these approximately 40 species are considered either suspect or proved to be Leishmaniosis vectors. The objective of this work was to monitor the phlebotominic fauna relating it to environmental alterations and climatic elements. The researched area was the one of construction of the barrage of the Hydroelectric Power Plant Capim Banco I, in Araguari river basin, in Uberlândia, MG, before and during the construction, and after the filling of the lake. The barrage of the Hydroelectric Plant Capim Branco I was built in the latitude 18° 47'25"S and longitude 48°08'50"W, in the Km 150 of Araguari river, starting in its. This research was accomplished from May 2003 to December 2006, being initiated by a demarcation of the plots for captures. Two capture plots were chosen in the area of the Hydroelectric Plant. The first plot was set beside the bridge of Pau Furado and the second one approximately 184m of the edge of the river. To capture the phlebotomine Shanon traps were used with the light of a gas lantern with screens of 500 candles, 3 luminous traps of CDC type (Center on Disease Control), with 6-volt batteries each, and suction tube, capturer of Castro. In order to study the environmental dynamics of the area, an Ecological Profile was developed. 87 captures were accomplished with 522 hours of field work and 1500 hours of laboratory work. 301 phlebotomine of two genders being 160 Brumptomyia and 141 Lutzomyia. 199 were captured in the CDC traps and 104 in the Shannon trap. 135 were male and 166 female. The capture of two species responsible for carrying ACL (L. whitmani and L. neivai) and the species responsible for carrying AVL in the Southeast Area (L. longipalpis), shows the necessity of a System of Environmental Surveillance in Health with prevention actions and phlebotomine control, in order to avoid risks to the residents of the settlement "Vila Nova" as well as to the visitors looking for leisure and fishing.